The Impact of Online Advertising and Attitude on Consumer Purchase Intentions in the Food and Beverage Industry (Jurnal Manajemen Bisnis, 2024)
The era of globalization has ushered in a heightened level of competition in the marketing landscape. This heightened competition among products in the market prompts manufacturers to engage in extensive promotional activities to capture consumer attention. With this backdrop, this research endeavors to explore the impact of Online Advertising and Consumer Attitudes on Consumer Purchase Intentions. The study adopted a random sampling approach and utilized a quantitative survey method, targeting a population size of 100, with a sample size of 80 respondents. Data analysis was conducted using multiple linear regression with IBM SPSS 29. The findings of the study unveil that Consumer Purchase Intentions are significantly influenced by both Online Advertising and Consumer Attitudes. Regression analysis underscores the positive and significant influence of consumer attitudes on purchase intentions, with a coefficient of 0.348, while online advertising exerts a positive impact with a coefficient of 0.314. In light of the research findings, the Adjusted R Square percentage stands at 57.4%, indicating that Online Advertising and Consumer Attitudes collectively contribute to a substantial 57.4% influence on Consumer Purchase Intentions. The remaining 42.6% variance is attributed to other unexplored factors. These findings underscore the pivotal role of online advertising and consumer attitudes in shaping consumer purchase behaviors in today's highly competitive market environment.